Variation in the nuclear effects of infection by different human rhinovirus serotypes - Walker, Erin J.; Jensen, Lora M.; Croft, Sarah; Ghildyal, Reena (Frontiers in Microbiology, 2015)
Human rhinovirus (HRV) is a positive sense RNA virus, which, despite replicating in the cytoplasm, has a significant impact on nuclear transport and nuclear localisation of host proteins. A number of studies have identified differences between HRV serotypes, with respect to host response, protease activity and replicative ability. Here we report the sero-specific effects of two group-A human rhinovirus serotypes, the minor group HRV2 and the major group HRV16, on nuclear transport and nuclear protein localisation. Using Western analysis, immunofluorescence and real time PCR, we show that HRV2 replicates at a faster rate than HRV16, which correlates with earlier production of viral proteases and disruption of host nuclear transport. There is significant variation in the nuclear effects of different rhinovirus species, which in turn may impact disease progression and patient response.